Sclerotherapy for Oral Pyogenic Granuloma – A case report - Regmee, Pragya; Rimal, Jyotsna; Maharjan, Iccha Kumar; Pandey, Sushma; Niroula, Deepa; Luitel, Abhinaya (Journal of College of Medical Sciences-Nepal, 2017)
First described by Hullihen in 1844, Pyogenic granuloma (PG) is a benign, exophytic vascular tumor. It is not infective, purulent or granulomatous but a reactive inflammatory mass of blood vessels with few fibroblasts within the mucosa or skin. Without any general agreement, there exist a variety of treatment options (complete surgical resection, cryosurgery, curettage, lasers etc). However, recurrence has been frequently reported. Sclerotherapy in PG (a vascular tumor) is not as commonly reported as in cases of hemangioma. Herein, we present a case of twenty-eight years old female with a clinical diagnosis of PG, treated with intralesional sodium tetradecyl sulfate (STS). Intralesional injection of 0.2 ml of undiluted STS was given for three visits between 10th of January and 21st of February 2016. The lesion healed completely at the patient’s fourth visit and recurrence was not reported till the patient was followed up for one year, i.e February 2017.